Torture is a form of colonial oppression in the face of the Algerian revolution of purification - Megder, Nour El-Din (The Algerian Historical Journal, 2026)
To confront the Algerian liberation revolution, the French occupation authorities used many forms of repression against the Algerians, including; Torture, which was used in various ways and imposed on patriots and suspects, and affected tens of thousands of Algerians and many segments of society, given that the person arrested is suspicious, and therefore must go through the stages of torture until his fate is determined. In this article, we will address: Colonial torture and its types and the methods used against the Algerians during the liberation revolution within the framework of forms of colonial oppression to confront the liberation revolution.These inhuman methods and methods were practiced against the Algerians during the liberation revolution in order to abandon their cause; It has had negative effects on Algerian society and continues to this day, and is considered a crime of French colonialism in Algeria.